Sodium aescinate inhibits microglia activation through NF-κB pathway and exerts neuroprotective effect - Xu, Fei; Jiang, Yiguo; Wang, Xiaoyu; Shen, Li; Yan, Yan; Guo, Dongkai; Wang, Cheng (Frontiers in Pharmacology, 2023)
Background: Microglia are resident immune cells of the central nervous system. Dysfunctional microglia produce toxic mediators that lead to neuronal death. Recent studies suggest that Sodium Aescinate (SA) has a neuroprotective effect. However, it is unclear whether SA exerts neuroprotective effects by inhibiting activation of microglia. Method: Traumatic brain injury (TBI) and lipopolysaccharide (LPS) neuroinflammation model were used to evaluate the microglia activation in vivo. BV2 and primary microglia cells were used to assess the microglia activation in vitro. Molecular docking technique was used to predict the binding energy of SA to NF-κB signaling pathway proteins. Result: SA inhibited the activation of microglia in TBI and LPS mouse models. SA also inhibited the expression of inflammatory proteins in BV2 and primary microglia cells. Western blot experiment showed that SA inhibited the activation of NF-κB pathway in BV2 and primary microglia cells.Molecular docking results also showed that SA had a better affinity with the core protein of the NF-κB pathway. In TBI model and conditioned medium experiment, SA pretreatment inhibited inflammation and protected neuron. Conclusions: Our study confirmed that the protection effects of SA on neurons by inhibiting microglial activation through NF-κB pathway.